Optimasi Biaya Rehabilitasi Saluran Irigasi Dengan Pendekatan Value Engineering (VE) Menggunakan Metode Paired Comparison - Mario Ferdiansyah; Nanda, Mahdika Putra; Suhana, Nono; Sunaryo, Sunaryo (Jurnal Rekayasa Infrastruktur, 2025)
The rehabilitation of irrigation channels is essential to improving the efficiency of agricultural water distribution. This study analyzes alternative irrigation channel designs in the D.I Macan Subang project using a Value Engineering (VE) approach with the Paired Comparison method. The existing design uses U-Ditch, which was compared to three alternatives: stone masonry, conventional ferosemen concrete, and geomembrane. The analysis shows that geomembrane provides the highest cost efficiency, with a total cost of IDR 562,075,772.46, resulting in savings of IDR 203,807,083.26 (26.61%) compared to the existing U-Ditch design. The Paired Comparison method effectively evaluates alternatives based on cost and technical criteria. This research contributes to cost-efficient irrigation design decision-making.